2013
DOI: 10.1242/jcs.118190
|View full text |Cite
|
Sign up to set email alerts
|

cGMP-dependent Protein Kinase Iβ Regulates Breast Cancer Cell Migration and Invasion via a Novel Interaction with the Actin/Myosin-associated Protein Caldesmon

Abstract: SummaryThe two isoforms of type I cGMP-dependent protein kinase (PKGIa and PKGIb) differ in their first ,100 amino acids, giving each isoform unique dimerization and autoinhibitory domains. The dimerization domains form coiled-coil structures and serve as platforms for isoform-specific protein-protein interactions. Using the PKGIb dimerization domain as an affinity probe in a proteomic screen, we identified the actin/myosin-associated protein caldesmon (CaD) as a PKGIb-specific binding protein. PKGIb phosphory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 71 publications
2
29
0
Order By: Relevance
“…SP also enhanced cGMP levels in MCF-7 and MDA-231 tumor xenografts (Figure 1B). Both MCF-7 and MDA-231 cells express cGMP-dependent PK G-1β (24, 25). To measure its enzymatic activity we monitored phosphorylation of Ser 239 of the endogenous PKG substrate, VASP.…”
Section: Resultsmentioning
confidence: 99%
“…SP also enhanced cGMP levels in MCF-7 and MDA-231 tumor xenografts (Figure 1B). Both MCF-7 and MDA-231 cells express cGMP-dependent PK G-1β (24, 25). To measure its enzymatic activity we monitored phosphorylation of Ser 239 of the endogenous PKG substrate, VASP.…”
Section: Resultsmentioning
confidence: 99%
“…Using wild-type and mutant PKGIβ D/D domains as affinity probes in a proteomic screen and we identified the actin/myosin associated protein caldesmon as a PKGIβ specific interacting protein [2]. Using immunofluorescent staining, we found that PKGIβ and CaD colocalized with F-actin at lammellipodial structures at the edge of MDA-MB-231 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Elevated expression of this protein was also observed in oral SCCs (Méndez et al., ) and its overexpression was associated with lymph node metastasis and poor prognosis in patients with oral cavity SCC (Chang et al., ). Additionally, it was shown that CALD1 phosphorylation reduced its binding to actin and myosin thus promoting pro‐migratory and pro‐invasive activities in breast cancer cells (Schwappacher et al., ). Hence, we hypothesised that de‐phosphorylation of CALD1 in HFs co‐cultured with HKs and FaDu cells or in SCCFs co‐cultured with FaDu cells shown in this study may significantly contribute to contractile activity, promote formation of actin stress fibres and reduce cell motility during transition of fibroblast to MFs or CAFs.…”
Section: Discussionmentioning
confidence: 99%